2003
DOI: 10.1111/j.1468-2443.2005.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior and Performance of Foreign Investors in Emerging Equity Markets: Evidence from Taiwan

Abstract: This study investigates trading behavior and investment performance of foreign investors in 60 large-size firms listed on the Taiwan Stock Exchange. Strong evidence is found that foreign investors employ momentum strategies of buying past winners and selling past losers and favor large-size, high book-to-market, and high-tech stocks, while no evidence is found that foreign investors herd on market consensus. Findings show that foreign investors are short-term superior performers but long-term inferior performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…For a majority of the sectors analyzed, we do not find any evidence in favor of herd formation during periods of large market swings. This finding is consistent with Lin and Swanson (2003) who tested whether foreign investors herd in the Taiwanese stock market using the same methodology. Similar to their findings, our regressions yield statistically significant and positiveˇestimates indicating that equity return dispersions increase during periods of large price changes as predicted by CAPM.…”
Section: Datasupporting
confidence: 92%
See 3 more Smart Citations
“…For a majority of the sectors analyzed, we do not find any evidence in favor of herd formation during periods of large market swings. This finding is consistent with Lin and Swanson (2003) who tested whether foreign investors herd in the Taiwanese stock market using the same methodology. Similar to their findings, our regressions yield statistically significant and positiveˇestimates indicating that equity return dispersions increase during periods of large price changes as predicted by CAPM.…”
Section: Datasupporting
confidence: 92%
“…With the exception of Tan et al (2008), prior studies generally provide results in favor of the rational asset pricing theories and conclude that herding is not an important factor in determining security returns during periods of market stress. In a limited study using sixty highest capitalization stocks held by foreign investors in Taiwan, Lin and Swanson (2003) employ the cross-sectional standard deviation based methodology and find no evidence that foreign investors herd in this market.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding more variables to the examination of characteristics of foreign ownership in Taiwan's market, Lin and Swanson (2003) found that large market capitalization, high book to market ratios and high-tech firms appeared to be leading factors, whilst earnings to price ratio, debt ratio and return volatility are insignificant variables.…”
Section: Characteristics Of Stock Holdings By Domestic and Foreign Inmentioning
confidence: 99%